Multimodality treatment of undifferentiated pleomorphic soft tissue sarcoma of the extremity (eUPS) in the elderly. Issue 5 (May 2022) - Bleckman, Roos F.; Acem, Ibtissam; van Praag, Veroniek M.; Dorleijn, Desirée M.J.; Verhoef, Cornelis; Schrage, Yvonne M.; Haas, Rick M.L.; van de Sande, Michiel A.J.; the collaborative Persarc research group,; ,; Bonenkamp, Han; van Ginkel, Robert J.; et al.
Abstract: Introduction: This subgroup analysis of undifferentiated pleomorphic soft tissue sarcoma of the extremity (eUPS) from the PERSARC collaborative group aimed to achieve a more personalized multimodality treatment approach for primary eUPS in elderly patients. Material and methods: A multicenter retrospective study including primary high-grade eUPS surgically treated with curative intent between 2000 and 2016. Overall survival (OS), local recurrence (LR) and distant metastasis (DM) curves were calculated by Kaplan Meier analysis. Cox proportional hazard models were used to determine the effect of radiotherapy. Results: From a total of 2511 patients with extremity soft tissue sarcoma (eSTS) of the PERSARC study collaborative; 703 patients with eUPS were included in this study. In elderly patients with eUPS 5-year OS, LR and DM were 35.4 (95%CI 29.3–42.8), 17.7 (95%CI 12.7–22.6) and 24.6 (95%CI 19.1–30.1). eUPS was significantly less treated with radiotherapy compared with other eSTS, especially in elderly patients. Patients with R1-R2 margins treated with radiotherapy had about half the risk of developing LR compared with patients treated without radiotherapy (HR = 0.454, p = 0.033). Conclusion: Elderly patients with eUPS were less often treated with radiotherapy and showed higher LR. Nowadays, given an increasing life expectancy in elderly patients, multimodality treatment should be considered. Highlights: - Treatment with radiotherapy in patients with eUPS has a positive effect on local control. - Overall survival was lower in eUPS compared with other eSTS which could be attributed to an older age of patients developing eUPS. - eUPS showed more high-grade and larger tumours, however local recurrence and distant metastasis did not differ. - Especially elderly patients with eUPS were less often treated with radiotherapy and showed higher LR compared to younger patients. - Given an increasing life expectancy in elderly patients, treatment with radiotherapy should be considered.